2012
DOI: 10.1371/journal.pone.0032759
|View full text |Cite
|
Sign up to set email alerts
|

Two Odorant-Binding Proteins Mediate the Behavioural Response of Aphids to the Alarm Pheromone (E)-ß-farnesene and Structural Analogues

Abstract: BackgroundAphids are agricultural pests of great economical interest. Alternatives to insecticides, using semiochemicals, are of difficult applications. In fact, sex pheromones are of little use as aphids reproduce partenogenetically most of the time. Besides, the alarm pheromone, (E)-ß-farnesene for a great number of species, is difficult to synthesize and unstable in the environment. The search for novel semiochemicals to be used in population control can be efficiently approached through the study of the ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(147 citation statements)
references
References 41 publications
10
135
0
2
Order By: Relevance
“…NribOBP3 has a K i value of 5.2 μM for Eβ f, 20.2 μM for (− )-α -pinene and 30.7 μM for β -pinene. Therefore, MvicOBP3 and NribOBP3 could be involved in detecting and recognising Eβ f, which is consistent with previous reports of other aphid OBP3s [2][3][4] . MvicOBP3 seems to have a stronger binding affinity to these semiochemicals than NribOBP3 in the fluorescent competitive binding assay relative to the binding of NPN (Supplementary Figure 5).…”
Section: Comparison Of Mvicobp3 and Nribobp3 With Other Obps To Compsupporting
confidence: 92%
See 1 more Smart Citation
“…NribOBP3 has a K i value of 5.2 μM for Eβ f, 20.2 μM for (− )-α -pinene and 30.7 μM for β -pinene. Therefore, MvicOBP3 and NribOBP3 could be involved in detecting and recognising Eβ f, which is consistent with previous reports of other aphid OBP3s [2][3][4] . MvicOBP3 seems to have a stronger binding affinity to these semiochemicals than NribOBP3 in the fluorescent competitive binding assay relative to the binding of NPN (Supplementary Figure 5).…”
Section: Comparison Of Mvicobp3 and Nribobp3 With Other Obps To Compsupporting
confidence: 92%
“…This includes the detection of alarm pheromones. Research on the pea aphid, Acyrthosiphon pisum, has shown that the recognition of the alarm pheromone (E)-β -farnesene (Eβ f), and structurally related molecules, is mediated by ApisOBP3 and ApisOBP7 [2][3][4] . Homologous genes to ApisOBP3 have also been identified in other aphid species 5,6 and in other insects such as the hoverfly, Episyrphus balteatus (EbalOBP3) 3 and the brown plant hopper, Nilaparvata lugens (NlugOBP3) 7 with these OBPs showing an apparent high affinity for Eβ f. Indeed it was suggested that E. balteatus uses Eβ f as a kairomone to locate its aphid prey 8 .…”
mentioning
confidence: 99%
“…This phenomenon has been previously reported and attributed to formation of micelles when the concentration of the ligand is higher than its critical micelle concentration. Such micelles can encapsulate molecules of 1-NPN, thus enhancing the emitted fluorescence (42,43).…”
Section: Resultsmentioning
confidence: 99%
“…It is odoriferous, and terpene-like substances occur in other natural sources: the trail markers of red fire ants (Van der Meer et al, 1982), alarm pheromones of aphids (Sun et al, 2012), and even a defense substance of wild potato plants against aphids (Bruce et al, 2005). The limited number of recent investigations has revealed that FNS possesses a wide range of important biological activities such as antibacterial activity (Chehregani et al, 2010), antifungal activity (Al-Maskri et al, 2011), and free radical-scavenging activity (Sarikurkcu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%